2006
DOI: 10.1111/j.1538-7836.2006.02046.x
|View full text |Cite
|
Sign up to set email alerts
|

The complement component C5a induces the expression of plasminogen activator inhibitor-1 in human macrophages via NF-κB activation

Abstract: Summary. Background: Atherosclerosis is considered to be a chronic inflammatory disorder. Activation of the complement cascade is a major aspect of chronic inflammatory diseases. Complement components were identified in atherosclerotic plaques, and a correlation between adverse events and C5a plasma levels was found. These findings support the notion that complement activation contributes to development and progression of atherosclerotic lesions. Objectives: We investigated whether complement components C3a an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…6D). These results clearly demonstrate the effect of C5a stimulation in activating NF-B signaling in DCs and also suggest that C5a and LPS have a synergistic effect on NF-B activation in DCs, which are in agreement with the previous findings that C5a alone, or C5a cooperating with LPS, activates NF-B signaling in macrophages (20,32).…”
Section: C5a Stimulation Activates Nf-b Signaling In Dcssupporting
confidence: 82%
“…6D). These results clearly demonstrate the effect of C5a stimulation in activating NF-B signaling in DCs and also suggest that C5a and LPS have a synergistic effect on NF-B activation in DCs, which are in agreement with the previous findings that C5a alone, or C5a cooperating with LPS, activates NF-B signaling in macrophages (20,32).…”
Section: C5a Stimulation Activates Nf-b Signaling In Dcssupporting
confidence: 82%
“…16 ECs and macrophages 23 in atherosclerotic lesions were found to express C5aR, and the effect of C5a has been investigated. 6 After vascular injury, VSMCs show increased proliferation, migration, and synthetic capacity and play a critical role in vascular remodeling.…”
Section: C5ar Expression In Mouse Neointimal Plaque Tissue and In Vsmmentioning
confidence: 99%
“…This study has limitations, including the fact that we only measured PAI-1 mRNA in mononuclear cells, which may not reflect gene expression in other tissues. Previous studies have shown that other cell types, in addition to monocytes/macrophages, produce PAI-1 (28,29). However, sequential sampling of peripheral blood is the only practical method available at present to serially test gene expression over a short interval in a dynamic environment such as exists after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%